Determinants of Influenza and Pertussis Vaccination Uptake in Pregnancy: A Multicenter Questionnaire Study of Pregnant Women and Healthcare Professionals. Issue 6 (June 2019) - Wilcox, Christopher R.; Calvert, Anna; Metz, Jane; Kilich, Eliz; MacLeod, Rachael; Beadon, Kirsten; Heath, Paul T.; Khalil, Asma; Finn, Adam; Snape, Matthew D.; Vandrevala, Tushna; Nadarzynski, Tom; et al.
Abstract : Introduction: Uptake rates of antenatal vaccination remain suboptimal. Our aims were to determine (1) the acceptability of routine vaccination among pregnant women, (2) the confidence of maternity healthcare professionals (HCPs) discussing vaccination and (3) HCP opinion regarding the optimum healthcare site for vaccine administration. Methods: Separate questionnaires for pregnant women and HCPs were distributed within 4 national health service (NHS) trusts in South England (July 2017 to January 2018). Results: Responses from 314 pregnant women and 204 HCPs (18% obstetricians, 75% midwives, 7% unidentified) were analyzed. Previous/intended uptake of influenza and pertussis vaccination was 78% and 92%, respectively. The commonest reason for declining vaccination was feared side effects for their child. White British women (79%) were significantly more accepting of influenza [85% vs. 61%; odds ratio (OR) 3.25; 95% confidence interval [CI], 1.67–6.32] and pertussis vaccination (96% vs. 83%; OR 4.83; 95% CI: 1.77–13.19) compared with nonwhite British women. Among HCPs, 25% were slightly or not at all confident discussing vaccination. Obstetricians felt significantly more confident discussing pertussis vaccination than midwives (68% vs. 55% were very/moderately confident; OR 2.05; 95% CI: 1.02–4.12). Among HCPs, 53%, 25% and 16% thought vaccines should be administered in primary care (general practice), community midwifery and in hospital, respectively. Conclusion: Misconceptions exist regarding safety/efficacy of antenatal vaccination, and framing information towards the child's safety may increase uptake. Education of HCPs is essential, and vaccine promotion should be incorporated into routine antenatal care, with an emphasis on women from ethnic minorities. Administration of vaccines in primary care presents logistical barriers; however, support for alternative sites appears low among HCPs. Abstract : Supplemental Digital Content is available in the text.